Heterogeneous integration of WBG devices and magnetic components: manufacturing and design optimisation - Stratta, Andrea (2022)
Wide-bandgap semiconductor devices, such as the ones based on silicon carbide (SiC) and gallium nitride (GaN), have been one of the biggest disruptive innovations in power electronics. The properties of these materials allow designers to develop more efficient and power dense converters. However, making a simple substitution of a Si based device for the WBG counterpart rarely results in a performance gain sufficient to justify the increase in cost. The manufacturing and design paradigm has to change. Power electronics has always been a multi-disciplinary subject, but each discipline was traditionally pursued independently. At the converter design stage, given the problem complexity, the main task is often divided into smaller and simpler problems, each one belonging to a specific discipline. It is the Roman divide and rule ("divide et impera") technique. As a result, individual product classes, such as power modules, passive components, thermal management systems, gate drivers and converters, have been developed without full consideration of the inter-component interactions. Unfortunately, when WBG devices are used at higher switching frequencies, in more confined spaces, and at higher temperatures compared to silicon based applications, these complex inter-component interactions become more dominant and the divide and rule strategy reaches its limit. Further advances will only be made through greater levels of structural and functional integration in both design and manufacture. This work aim is to apply heterogeneous integration and design automation concepts to unlock the full potential of WBG semiconductor devices.